2005
DOI: 10.1021/om050612y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Salicylaldiminato-Functionalized N-Heterocyclic Carbene Complex of Nickel(II) and Its Catalytic Activity for Styrene Polymerization

Abstract: A novel potentially tridentate N-heterocyclic carbene (NHC) precursor, anionic salicylaldimine-functionalized imidazolium bromide, [3,5-t Bu 2 -2-(HO)C 6 H 2 CHdNCH 2 CH 2 (CH-{NCHCHN i Pr})Br] (HL‚HBr, 2), was designed. The reaction of in situ-generated monoanionic tridentate salicylaldiminato-functionalized NHC LNa with Ni(PPh 3 ) 2 Br 2 affords a novel monoligand Ni(II) bromide, [3,5-t Bu 2 -2-(O)C 6 H 2 CHdNCH 2 CH 2 (C{NCHCHN i Pr})]NiBr (LNiBr , 3), in good yield. Complex 3 can also be synthesized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 43 publications
4
60
0
Order By: Relevance
“…In particular, Pd-NHC complexes have been widely used in the making of C-C bonds often by employing the Mizoroki-Heck and Suzuki-Miyaura coupling reactions. Similarly, some Ni-NHC complexes have shown to be catalytically active for a wide range of reactions such as SuzukiMiyaura [21,22] and Kumada-Corriu [23][24][25][26][27][28] couplings, olefin dimerization [3] and polymerization, [29][30][31][32] C-C bond activation of biphenylene, [33] transfer hydrogenation of imines, [34] and amination [35] and dehalogenation [36] of aryl halides. Notably, most of these nickel complexes contain NHC ligands that are derived either from imidazole or imidazoline precursors, whereas the catalytic activity of Ni IIbenzimidazolin-2-ylidenes have rarely been studied.…”
Section: Kumada-corriu Catalysismentioning
confidence: 99%
“…In particular, Pd-NHC complexes have been widely used in the making of C-C bonds often by employing the Mizoroki-Heck and Suzuki-Miyaura coupling reactions. Similarly, some Ni-NHC complexes have shown to be catalytically active for a wide range of reactions such as SuzukiMiyaura [21,22] and Kumada-Corriu [23][24][25][26][27][28] couplings, olefin dimerization [3] and polymerization, [29][30][31][32] C-C bond activation of biphenylene, [33] transfer hydrogenation of imines, [34] and amination [35] and dehalogenation [36] of aryl halides. Notably, most of these nickel complexes contain NHC ligands that are derived either from imidazole or imidazoline precursors, whereas the catalytic activity of Ni IIbenzimidazolin-2-ylidenes have rarely been studied.…”
Section: Kumada-corriu Catalysismentioning
confidence: 99%
“…[86,[113][114][115][116] These key studies demonstrate that chelating ligand systems can provide a degree of stability against the facile reductive elimination process previously noted for monodentate NHC complexes of Ni. [24] However, it appears that the reductive elimination from these hemilabile systems may still lead to catalyst deactivation.…”
Section: A Number Of Examples Of Chelating Functionalised Nhc Complexmentioning
confidence: 59%
“…In the same way that phosphane-based ligands have undergone important design stages, novel df-NHC ligands are now being designed and their performance investigated; in further polymerisation studies, the Ni II complex 73 (Figure 17) was treated with NaBPh 4 and tested as a catalyst for the polymerisation of styrene, at 80°C in toluene. [114] On the basis of the relatively high average molecular weight of the resultant polymer it was suggested that the catalysts with a tridentate salicylaldiminato-carbene demonstrate higher stability. The same group also studied the polymerisation of styrene using a Ni II complex containing an NHC functionalised with a C3-bridged indenyl group, 74.…”
Section: A Number Of Examples Of Chelating Functionalised Nhc Complexmentioning
confidence: 99%
“…[6,7] Well re-solved 1 H NMR spectra of these ligands are reported in the Supporting Information; the assignments of the protonic resonances were based on previously reported data, and in the case of phimid-H·Br were corroborated by long-range 1 H-1 H COSY experiments. Recrystallisation of phimidH·Br from hexane/diethyl ether afforded crystals suitable for X-ray analysis.…”
Section: Synthesis and Characterisation Of The Ligandsmentioning
confidence: 94%
“…In particular we considered the salicylaldimine-functionalised imidazolium bromide ligand [3,5-tBu 2 -2-(OH)C 6 H 2 CH=NCH 2 CH 2 (CH{NCH-CHNiPr})]Br (phimid-H·Br), previously employed in the synthesis of N-heterocyclic carbene complexes of late transition and lanthanide metals. [6] Here we describe the synthesis, solution properties and reactivity of novel alkylaluminium complexes bearing the phimid-H·Br ligand. The distinctive behaviour of these complexes is compared with that of an analogous alkylaluminium complex bearing a salicylaldimine ligand lacking the pendant imidazolium moiety: 3,5-tBu 2 -2-(OH)C 6 H 2 CH= NiPr (phim-H).…”
Section: Introductionmentioning
confidence: 99%